Increased NK Cell Count in Multiple Sclerosis Patients Treated With Dimethyl Fumarate: A 2-Year Longitudinal Study - Marastoni, Damiano; Buriani, Alessandro; Pisani, Anna Isabella; Crescenzo, Francesco; Zuco, Carmela; Fortinguerra, Stefano; Sorrenti, Vincenzo; Marenda, Bruno; Romualdi, Chiara; Magliozzi, Roberta; Monaco, Salvatore; Calabrese, Massimiliano (Frontiers in Immunology, 2019)
Background: Dimethyl fumarate (DMF) is a disease-modifying drug for relapsing-remitting multiple sclerosis. Among others, DMF impedes immune activation by shifting the balance between inflammatory and regulatory cell types and by inducing apoptosis-triggered lymphopenia. Although the decrease in lymphocyte count is an early effect of the drug in several patients, the long-term impact on lymphocyte subsets is largely unknown. Methods: We performed a two-year observational study on total lymphocyte count and subsets thereof by flow cytometry of peripheral blood of 38 multiple sclerosis patients in treatment with DMF. Data were collected at the beginning and after 3, 6, 12 and 24 months of therapy. Results: Total lymphocyte count decreased in relation to the time of exposure to DMF. Mean absolute B cell count decreased by 34.1% (p <0.001) within the first three months of therapy and then remained stable over time. Mean absolute CD3+ T cells count decrement reached 47.5% after twelve months of treatment (p <0.001). NK cells count showed a heterogeneous trend, increasing by 85.9% (p <0.001) after two years of treatment. CD4+ T cells and CD8+ T cells substantially decreased, with a significant increase of CD4+/CD8+ ratio during the first year of therapy. Conclusions: NK cells showed a heterogeneous behaviour during DMF treatment with a significant increase over time. Since NK cells may also have a regulatory effect on immune system modulation, their increase during DMF treatment might play a role in the efficacy and safety of the drug.